ANALISIS EFEKTIVITAS PENGGUNAAN E-LEARNING BERBASIS GOOGLE SCHOLAR DALAM MENDUKUNG PEMBELAJARAN MAHASISWA JURUSAN BAHASA DAN SASTRA INDONESIA - Diyah, Nurfaadiyah Rahmi; Hikma; Abdul Haliq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
E-learning is a digital technology-based learning media that can make learning more flexible, independent, creative, and innovative. Many types of e-learning are now available on various types of platforms, one of which is Google Scholar. Google Scholar is a digital media that is widely used by students to support their learning, especially students majoring in Indonesian Language and Literature. This is because students majoring in Indonesian Language and Literature always have learning and assignments in the form of scientific papers. Thus, students in this department need a lot of reference material to be able to compile scientific papers from reliable sources. Therefore, this study aims to analyze the effectiveness of the use of Google Scholar-based e-learning digital media in supporting the learning of students majoring in Indonesian Language and Literature. The type of research conducted is descriptive qualitative research with data sources derived from interviews by 5 (one) informants of students majoring in Indonesian Language and Literature. The results of this study indicate that the use of digital e-learning media based on Google Scholar is effective in learning for students majoring in Indonesian Language and Literature because Google Scholar provides various sources of reliable and needed materials, makes it easy to write bibliographies that will be included in papers and articles, and also becomes a facilitator for students who do not have printed or physical books to find sources of materials for their paper and article writing assignments.